APAKAH KEPEMILIKAN INSTITUSIONAL MEMILIKI PERAN MODERASI DALAM HUBUNGAN PENGHINDARAN PAJAK DAN RISIKO PERUSAHAAN? - Al-Hazmi, Raldin Alif; Firmansyah, Amrie (Jurnal Akuntansi, 2024)
The practice of minimizing corporate tax payments may provide financial benefits to companies, but it also carries risks. As a result, taxation becomes a critical factor influencing corporate risk. This research explores how tax avoidance affects corporate risk, focusing on transportation and logistics sector companies listed on the Indonesia Stock Exchange from 2021 to 2023. The study incorporates institutional ownership as a moderating factor. Data were gathered from financial reports and stock prices available on platforms such as the Indonesia Stock Exchange website (www.idx.co.id), companies' official websites, and www.finance.yahoo.com. Using purposive sampling, a total of 39 observations were analyzed. Multiple linear regression analysis on panel data indicates that tax avoidance does not significantly affect corporate risk. Furthermore, institutional ownership mitigates the positive effect of tax avoidance on corporate risk. This study contributes to the literature for financial statement users and investors and serves as a resource for investors and potential investors in conducting analyses for making investment decisions in the Indonesian capital market.